“BECAUSE I LOVED HER SO MUCH”: GENDER-BASED VIOLENCE AND THE REPRESENTATIONS OF THE FEMININE IN THE MANGA TOMIE - Pereira, Fabrinne Rocha; Queiroz, Marta Maria Azevedo (Seven Editora, 2026)
This article, part of the research conducted for the Master’s in Communication (PPGCOM-UFPI, 2025), proposes an analysis of how violence against women and villainy are represented in the manga "Tomie," highlighting the ways in which narratives reinforce cultural and social norms that perpetuate such violence. This work by manga artist Junji Ito, known for his stories of psychological horror and supernatural elements, first published in 1987, revolves around the character Tomie, with the narrative—"an irresistibly beautiful young woman provokes obsession and violence in the men around her." This phrase summarizes the dramatic structure of the work, but also reveals, in deeper layers, a powerful commentary on how patriarchal culture constructs, controls, and punishes the female figure. The research adopted a qualitative approach, with content analysis (Bardin, 2006), observing 12 selected Figures from the manga, which were organized into five categories: 1) femicide, 2) nudity, 3) passion, 4) villainy, 5) male brotherhood, and 6) enchantment. Categories 1, 4, and 5 are analyzed in this article, from the theoretical perspectives of Beauvoir (2014), Segato (2013), Elena Teles and Valeska Zanello (2017), and Alves (2021). The analysis of violence against women in Tomie reveals not only Junji Ito’s skill in creating horror narratives, but also his ability to address profound social issues. Through Tomie’s story, we are confronted with the reality of obsession, objectification, and violence, themes that continue to resonate in contemporary society. The repetition of Tomie’s femicide and her regeneration throughout the narrative suggest a critique of the objectification and blaming of women. Therefore, concrete actions are urgent, considering the exponentially increasing rates of violence against women, producing profound impacts both on individual structures—especially those of female victims—and on the sociocultural dynamics that affect their families and communities.